Penerapan Media Board Game Zathura Mathematics Untuk Meningkatkan Motivasi Peserta Didik dalam Belajar Matematika - Dewi Wahyuningsih; Danang Setyadi (Journal on Education, 2019)
This study aims to increase motivation in IX-D students of SMP Negeri 2 Tuntang on the material of Rank Numbers and Root Shapes with the Zathura Mathematics Board Game media. This research is a classroom action research (CAR) conducted in two cycles and each cycle takes place four times in accordance with the learning implementation plan. The research was conducted in the odd semester learning process in August 2019. The subjects of this study were students of class IX-D SMP Negeri 2 Tuntang in the 2019/2020 academic year totaling 30 students consisting of 14 female students and 16 male students . The results showed that the use of Zathura Mathematics Board Game media can increase students' motivation to learn mathematics. The average value of students' motivation questionnaire in learning mathematics was 67% after the learning process was assisted with learning media. The motivation of students increased significantly by 14% after using the media, the average motivation of students to 81%.